How adequate is measles surveillance in the United States? Investigations of measles-like illness, 2010-2017 - Susannah L. McKay; Jessica Leung; Paul A. Gastañaduy; Janell A. Routh; Rafael Harpaz (Taylor & Francis Group, 2021)
Given the availability of an effective and safe vaccine, the World Health Organization (WHO) declared that global measles eradication is achievable, and measles elimination goals have since been established as interim steps toward eradication. As part of a strategy to maintain elimination, the Pan American Health Organization (PAHO) and WHO stipulate a minimum annual reporting rate of discarded non-measles cases of ≥2 per 100,000 population, in order to ensure sensitive surveillance and adequate investigative effort. With its effective vaccination program, the United States in 2000 was among the first countries to verify elimination, although subsequently, it has not routinely reported discarded rates. We estimated MLI investigation rates among insured individuals during 2010-2017, using data from the MarketScan® databases. We defined "MLI investigations" as measles serologic testing within 5 days following diagnostic codes for measles-compatible symptoms and conditions. We provide a rationale for pre-specifying three subgroups for analysis: children aged ≤15 years; males aged 16-22 years excluding data from summer months; and males aged ≥23 years. MLI investigation rates ranged from 6.6─26.4 per 100,000, remaining stable over time except during the 2015 measles outbreaks when rates increased, particularly among young children. In addition to high vaccine uptake, measles elimination requires ongoing vigilance by clinicians and high-quality, case-based surveillance. Estimated rates of MLI investigations in this U.S. population suggesting that the quality of measles surveillance is sufficiently sensitive to detect endemic measles circulation if it were to be occurring.